2015
DOI: 10.1242/dev.112946
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Med23 deficiency enhances neural differentiation of murine embryonic stem cells through modulating BMP signaling

Abstract: Unraveling the mechanisms underlying early neural differentiation of embryonic stem cells (ESCs) is crucial to developing cell-based therapies of neurodegenerative diseases. Neural fate acquisition is proposed to be controlled by a 'default' mechanism, for which the molecular regulation is not well understood. In this study, we investigated the functional roles of Mediator Med23 in pluripotency and lineage commitment of murine ESCs. Unexpectedly, we found that, despite the largely unchanged pluripotency and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In the current study, through WES, one variant in the MED23 gene was suggested for ID. This gene is a key regulator of the protein‐coding gene expression and is involved in adipogenesis, chromatin modification, neural differentiation, proliferation, smooth muscle cell differentiation, and tumorigenesis . Mutations in this gene have been associated with several disorder, including cancer as well as, cardiovascular and neurodevelopmental diseases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, through WES, one variant in the MED23 gene was suggested for ID. This gene is a key regulator of the protein‐coding gene expression and is involved in adipogenesis, chromatin modification, neural differentiation, proliferation, smooth muscle cell differentiation, and tumorigenesis . Mutations in this gene have been associated with several disorder, including cancer as well as, cardiovascular and neurodevelopmental diseases .…”
Section: Discussionmentioning
confidence: 99%
“…This gene is a key regulator of the protein-coding gene expression and is involved in adipogenesis, chromatin modification, neural differentiation, proliferation, smooth muscle cell differentiation, and tumorigenesis. 5,22,26 Mutations in this gene have been associated with several disorder, including cancer as well as, cardiovascular and neurodevelopmental diseases. 10,27,28 Loss of function of the MED23 gene in the early developmental stages causes neurological disorders, whereas somatic mutations and variations in expression levels, play roles in the development of different kind of cancer later in life, including breast cancer, lung cancer, liver cancer, esophageal cancer, and Colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complete set of roles played by Med23 are incompletely understood, it has been shown to modulate signaling by the BMP, Ras/ELK1, and RhoA/MAL pathways (45,46). Thus it has the potential to regulate a variety of genes, including potentially voltage-gated potassium channels or interacting 36 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 477 478 479 480 481 proteins thereof.…”
Section: Novel Putative Gene/electrophysiology Relationshipsmentioning
confidence: 99%
“…One hypothesis for how Rab33a could regulate AHP amplitude and/or AP half-width is that Rab33a might facilitate the transport and/or insertion of vesicles containing voltage-gated potassium channels, or regulators thereof, into the axonal membrane, leading to narrower action potentials and larger AHPs. Our analysis of the AIBS data suggests that any effects of Rab33a expression on AHP amplitude would be present only in inhibitory cell types.Med23 (also known as Crsp3), a subunit of the mediator complex which acts as a transcriptional coactivator for RNA polymerase II (43,44), shows a positive correlation with AHP amplitude (Fig 7D).Although the complete set of roles played by Med23 are incompletely understood, it has been shown to modulate signaling by the BMP, Ras/ELK1, and RhoA/MAL pathways (45,46). Thus it has the potential to regulate a variety of genes, including potentially voltage-gated potassium channels or interacting 36 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 477 478 479 480 481 proteins thereof.…”
mentioning
confidence: 99%
“…MED16/SFR6 was first identified for its role in freezing tolerance and MED25/PFT1 for its role in promoting flowering (Knight 1999; Cerdán and Chory 2003). Since then, both have been shown to function extensively in the regulation of defense-related genes, as well as a number of other processes (Boyce et al 2003; Knight et al 2009; Kidd et al 2009; Elfving et al 2011; Xu and Li 2011; Wathugala et al 2012; Chen et al 2012; Çevik et al 2012; Sundaravelpandian et al 2013; Hemsley et al 2014; Yang et al 2014; Raya-González et al 2014; Zhang et al 2014; Seguela-Arnaud et al 2015; Zhu et al 2015; Wang et al 2016; Muñoz-Parra et al 2017; Dolan et al 2017). MED2 has been less well studied, but has been shown to share some functions with MED14 and MED16 in cold-regulated gene expression (Hemsley et al 2014).…”
mentioning
confidence: 99%